Sex-Specific Odorant Receptors of the Tobacco Hornworm Manduca Sexta - Grosse-Wilde, Ewald; Stieber, Regina; Forstner, Maike; Krieger, Jürgen; Wicher, Dieter; Hansson, Bill S. (Frontiers in Cellular Neuroscience, 2010)
As odor information plays a vital role in the life of moths, their olfactory sense has evolved into a highly specific and sensitive apparatus relevant to reproduction and survival. The key players in the detection of odorants are olfactory receptor (OR) proteins. Here we identify four OR-encoding genes differentially expressed in the antennae of males and females of the sphingid moth Manduca sexta. Two male-specific receptors (the previously reported MsexOR-1 and the newly identified MsexOR-4) show great resemblance to other male moth pheromone ORs. The putative pheromone receptors are co-expressed with the co-receptor involved in general odorant signal transduction, the DmelOr83b homolog MsexOR-2. One female-specific receptor (MsexOR-5) displays similarities to BmorOR-19, a receptor in Bombyx mori tuned to the detection of the plant odor linalool.